More evidence for an admixture of the Hyles euphorbiae complex's main lineages in Mediterranean Europe (Lepidoptera: Sphingidae) - Michael B. MENDE; Anna K. HUNDSDOERFER (European Journal of Entomology, 2014)
The populations of the Hyles euphorbiae complex on Crete and the Dodecanese Islands have been described as an endemic species, Hyles "cretica". Alternatively, they are thought to be of hybrid origin from the complex's two main lineages, the European H. euphorbiae and African H. tithymali, because of their intermediate morphology. That they belong to a discrete taxon is supported by the fact that all the recent samples analyzed belong to an endemic mitochondrial haplotype cluster; however, this cluster is so close to the tithymali cluster that it might also be regarded as a sublineage of H. tithymali. Similarly, southern Italy is currently dominated by another distinct tithymali-related cluster, named "italica". However, sequencing of historic museum specimens, which were collected in Italy during the past century, revealed that mitochondrial haplotypes of H. euphorbiae were once present throughout the entire range of "italica" thus contradicting a long-term isolated evolution of a southern Italian refugial entity. In the present study we likewise sequenced the few available historic specimens from the Aegean Islands and also found a specimen from Crete which belonged to the euphorbiae cluster. In conclusion, southern Italian and southern Aegean populations both appear to be dynamic hybrid mixtures of the European H. euphorbiae and African H. tithymali, rather than separately evolved taxa.